(untitled) (Journal of the College of Basic Education, 2022)
The task of this study is to dig into the three layers of the poet’s poetic textThe Iraqi Yassin Taha Hafez reached the beauty of the place in its overlaps and these three layersThey are: the first - the surface layer, and it is dealt with by the Sakia method; The second - classCentral and dealt with externally with the appearance of the place. The third is the deep layer, which is a methodFusion in the blood of the text and give it new qualities. The research will deal with the third layer because it is the critical method that pleads with the placethe sentimental poet who poetically transforms himself; Let us reflect the beauty of the place through fusionThe dissolution within the text and the use of space in the general structure has a distinct artistic prowess that reformulatesPlaces and arranging them in a tight arrangement that releases the energies of the text and feeds it with new blood.